THE INFLUENCE OF THE REGIONAL ACCOUNTING FINANCIAL SYSTEM USING INFORMATION TECHNOLOGY AND INTERNAL CONTROL SYSTEMS ON THE QUALITY OF FINANCIAL REPORTING IN DIBAL VILLAGE NGEMPLAK DISTRICT BOYOLALI - Utami, Wikan Budi; Doaji, Doaji; Pratiwi, Desy Nur (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research is a type of quantitative research that aims to determine the effect of the regional accounting financial system, the use of information technology, and the internal control system on the quality of financial reports in the village of Dibal Ngemplak Boyolali. The type of data used in this study is primary data obtained directly from respondents by distributing questionnaires and literature. The sample of this research is all the apparatus of Dibal Ngemplak Boyolali Village, totaling 60 respondents. The sampling technique in this study used a purposive sampling technique. The data in this study were processed using SPSS IBM Statistics Software Version 18. The results of this study revealed that the influence of the regional accounting financial system, the use of information technology, and the internal control system had an effect on the quality of the financial reports of the Dibal Ngempalk Boyolali Village Government. Keywords: Regional Financial Accounting System, Utilization of Information Technology, Internal Control Systems, Quality of Financial Reports